KEHIDUPAN MANUSIA SILVER DI KOTA PEKANBARU - Laos Maria Manullang; Rina Susanti (Nusantara Hasana Berdikari, 2022)
This research was conducted on Silver Man who was in Pekanbaru City with the aim of knowing the life of Silver Man who worked at traffic lights and the background of Silver Man's actions in choosing to work as a beggar. Qualitative research with research subjects selected with Non-probability sampling techniques. Data collection techniques use observation, interviews, and documentation with data analysis, namely data collection, data reduction, data presentation and drawing conclusions. The results of this study show that the life of The Silver Man in Pekanbaru City can be seen from the activities carried out daily. Before carrying out their activities as Silver Humans, usually they will make some preparations such as leaving for the location on time, for the preparation of tools and materials to be used, then continued by painting the body, waiting for the drying of the paint on the skin. The activities carried out by The Silver Man in Pekanbaru City lasted until the afternoon until the evening. The background of the actor's actions as a Human is due to economic factors, outcome opportunities, follow-up, closed identities and resources contained in the crowds, art, traffic lights located in Pekanbaru City.